Respuesta :
Hey Phillip!
5y + 2 - 3(4y) = 0
5y + 2 - 12y = 0
-7y + 2 = 0
Then subtract 2 on both sides
-7y + 2 - 2 = 0 - 2
-7y = -2
Divide both sides by -7
-7y/-7 = -2/-7
y = 2/7
Let me know if you have any question. As always, it is my pleasure to help students like you!
5y + 2 - 3(4y) = 0
5y + 2 - 12y = 0
-7y + 2 = 0
Then subtract 2 on both sides
-7y + 2 - 2 = 0 - 2
-7y = -2
Divide both sides by -7
-7y/-7 = -2/-7
y = 2/7
Let me know if you have any question. As always, it is my pleasure to help students like you!